Genetic Diversity Analysis in Taro Using Molecular Markers . An Overview - Asha Devi, A (JOURNAL OF ROOT CROPS, 2013)
Taro (Colocasia esculenta L. (Schott.)) is an important root crop especially in the humid tropics and sub-tropics. It is one of the few crops that can adapt well to different agro-climatic conditions. Taro is thought to have been originated in the Indo-Malayan region probably in North Eastern India and Bangladesh. However, some studies suggest that there exists a parallel Pacific gene pool for taro, quite distinct from the Asian one. Due to the vegetative nature of the crop and as a result of fixing of somatic mutations, morphotypes are quite distinct even when they share the same genetic material. Hence, for breeding purposes, selection of the most divergent parents becomes difficult if one goes by morphological characterization alone. It is in this regard that molecular characterization attains its relevance. Here, the actual genetic diversity exhibited by the crop can be measured and utilized for breeding and conservation of genetic resources. Though a good amount of molecular work has been carried out in the Pacific and South-east Asian genepools, no systematic work has been undertaken in Indian taro germplasm collections, except for a few scattered reports. In this review, an attempt has been made to document thoroughly the major molecular markers used for the analysis of genetic diversity in taro and its application in the management of genetic resources.